Introduction Situation Background Assessment Recommendation (ISBAR) Checklist to Improve Nurses’ Handover Quality - Lena Yulianti; Kuswantoro Rusca Putra; Lilik Supriati; Yulian Wiji Utami; Aat Djanatunisah; Winda Yuniarsih (Babali Nursing Research)
Background: Patient transfer between hospital units, especially from the Emergency Department (ED) to the High Care Unit-Intensive Care Unit (HCU-ICU), carries a high risk of adverse events due to communication failures during handover. The Introduction, Situation, Background, Assessment, Recommendation (ISBAR) checklist is a structured communication tool designed to enhance handover quality but is underutilized in written patient transfer. This study aimed to evaluate the effectiveness of the ISBAR checklist in improving the quality of nurse handovers during ED to HCU-ICU patient transfers.